Montreal Brain Injury Vision Screening Test for General Practitioners - Abbas Farishta, Reza; Farivar, Reza (Frontiers in Human Neuroscience, 2022)
Visual disturbances are amongst the most commonly reported symptoms after a traumatic brain injury (TBI) despite vision testing being uncommon at initial clinical evaluation. TBI patients consistently present a wide range of visual complaints, including photophobia, double vision, blurred vision, and loss of vision which can detrimentally affect reading abilities, postural balance, and mobility. In most cases, especially in rural areas, visual disturbances of TBI would have to be diagnosed and assessed by primary care physicians, who lack the specialized training of optometry. Given that TBI patients have a restricted set of visual concerns, an opportunity exists to develop a screening protocol for specialized evaluation by optometrists—one that a primary care physician could comfortably carry out and do so in a short time. Here, we designed a quick screening protocol that assesses the presence of core visual symptoms present post-TBI. The MOBIVIS (Montreal Brain Injury Vision Screening) protocol takes on average 5 min to perform and is composed of only ‘high-yield’ tests that could be performed in the context of a primary care practice and questions most likely to reveal symptoms needing further vision care management. The composition of our proposed protocol and questionnaire are explained and discussed in light of existing protocols. Its potential impact and ability to shape a better collaboration and an integrative approach in the management of mild TBI (mTBI) patients is also discussed.